2012
DOI: 10.1111/j.1574-6968.2012.02626.x
|View full text |Cite
|
Sign up to set email alerts
|

Eudragit E100® potentiates the bactericidal action of ofloxacin against fluoroquinolone-resistant Pseudomonas aeruginosa

Abstract: We report the enhanced bactericidal activity of ofloxacin in drug‐containing Eudragit E100® dispersions (EuCl‐OFX) against Pseudomonas aeruginosa and the effect of the cationic polymer on bacterial membrane. Organisms treated with EuCl‐OFX showed changes in cell morphology, altered outer membrane (OM) and cytoplasm with low electrodensity areas. Zeta potential of bacterial surface was shifted to positive. Sensitization to lytic agents was also observed. A profound effect on bacterial size, granularity and memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 21 publications
(22 reference statements)
3
22
0
Order By: Relevance
“…3C and 4). Accordingly, enhanced bacterial uptake of OFX loaded bioadhesive hydrogels or OFX-containing Eudragit E100 ® dispersions were reported to increase bactericidal properties against P. aeruginosa [29,30]. In the present study, OFX-mPEG-PLGA nanoparticles consistently showed better bactericidal activity against all the tested pathogenic bacterial strains, as revealed by the severe reduction in the number of colonies than the free drug or OFX-PLGA nanoparticles ( Fig.…”
Section: Discussionsupporting
confidence: 61%
“…3C and 4). Accordingly, enhanced bacterial uptake of OFX loaded bioadhesive hydrogels or OFX-containing Eudragit E100 ® dispersions were reported to increase bactericidal properties against P. aeruginosa [29,30]. In the present study, OFX-mPEG-PLGA nanoparticles consistently showed better bactericidal activity against all the tested pathogenic bacterial strains, as revealed by the severe reduction in the number of colonies than the free drug or OFX-PLGA nanoparticles ( Fig.…”
Section: Discussionsupporting
confidence: 61%
“…EuE100 spectrum presents the characteristic bands at 1730 and 2770-2820 cm À1 associated to ester and diethylamine groups. 40 On the other hand, EuS100 peaks are observed: 2950, 1730 and 1450 cm À1 due to carboxylic oxydryl, ester and methyl groups, respectively. 41 Black arrows indicate shifts from 1780-1730 to 1760 cm À1 which can be associated to polymers interactions related to the blend formation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that Eudragit shows a membrane-destabilising effect that is expressed as a perturbation of the membrane structure allowing the passage of water-soluble molecules, and also antiviral effects against the herpes simplex virus type 2 (HSV-2) [37]. Formulations with traditional antibiotics have also been described using Eudragit to increase their activity against P. aeruginosa with fluoroquinolone resistance [38]. Therefore, the encapsulation of the peptide +2 and the peptide +5 into CL increases the activity by 2083 (peptide+2/CL-peptide+2) and 1562 times (peptide+5/CL-peptide+5) against L. monocytogenes .…”
Section: Resultsmentioning
confidence: 99%